A novel three-stage risk-based scheme to improve power system resilience against hurricane. (July 2021) - Mahzarnia, Maedeh; Moghaddam, Mohsen Parsa; Haghifam, Mahmoud-Reza
Highlights: A three-stage resilience enhancement scheme includes two techniques. Transmission line switching is used when cascading failures are not probable. Preventive islanding is used when cascading failures are likely to occur. The resilience improvement amount is assessed using a holistic evaluation approach. Abstract: This paper introduces a three-stage resilience improvement scheme to enhance operational power system resilience against a hurricane event. As a prerequisite for implementing this scheme, the hurricane impact on the power system is modeled using a stochastic model in which a set of transmission line failure scenarios is generated. This scheme is composed of three stages: (i) Employing an approach for vulnerability assessment of each scenario to identify the scenarios in which cascading failures are likely (or not likely) to occur; ( ii) Implementing optimal transmission line switching (OTLS) technique for those scenarios in which cascading failures are not much probable; (iii) Implementing preventive islanding (PI) technique for the scenarios in which cascading failures are probable. The amount of resilience improvement is assessed using a two-step risk-based framework. The applicability of the proposed methodology is examined by implementing it in the IEEE 24-bus test system. Graphical abstract: Image, graphical abstract